PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA MATERI TEKNOLOGI UNTUK KEHIDUPAN DI KELAS V UPTD SD NEGERI OEBOBO 2 KOTA KUPANG - Daepanie, Dorce Agnes; Koroh, Taty R.; Nawa, Netty E. A. (Universitas Nusa Cendana, 2024)
The purpose of this study is to improve student learning outcomes in class VA science subjects through the application of the problem-based learning model. The research method used is Classroom Action Research (PTK) consisting of four stages, namely: planning, implementation, observation, and reflection. This research was conducted at UPTD SD Negeri Oebobo 2, Kupang City. The research subjects were students in the VA UPTD class at SD Negeri Oebobo 2, Kupang City, consisting of 27 students. Data collection techniques are in the form of observation and tests, while the data analysis techniques used are qualitative descriptive and quantitative descriptive. In cycle I, the teacher's observation results received an average score of 76.47 the results of observing student activities were 63.42, and the average learning outcome score was 68.51 with a classical completeness of 66.66% with a good predicate (B). In cycle II, the teacher's observation results received an average score of 94.11 the results of observing student activities were 82.63, and the average learning outcome score was 82.22 with a classical completeness of 92.59% with a very good (BS) predicate. So the problem-based learning model can improve student learning outcomes. The results of this research show that learning using the problem-based learning model on technology for life material can improve the learning outcomes of students in the VA UPTD class at SD Negeri Oebobo 2, Kupang City.